Obtaining information from family caregivers to inform hospital care for people with dementia: A pilot study. (10th January 2019) - Toye, Christine; Slatyer, Susan; Quested, Eleanor; Bronson, Mary; Hill, Andrew; Fountaine, Janet; Uren, Hannah V.; Troeung, Lakkhina; Maher, Sean
Abstract: Aim: We aimed to implement a systematic nurse–caregiver conversation, examining fidelity, dose and reach of implementation; how implementation strategies worked; and feasibility and mechanisms of the practice change. Background: Appropriate hospital care for people living with dementia may draw upon: information from the patient and family caregiver about the patient's perspective, preferences and usual support needs; nursing expertise; and opportunities the nurse has to share information with the care team. Within this context, planned nurse–caregiver communication merits further investigation. Methods: In Phase I, we established the ward staff's knowledge of dementia and Alzheimer's disease, prepared seven nurse change leaders, finalised the planned practice change and developed implementation plans. In Phase II, we prepared the ward staff during education sessions and leaders supported implementation. In Phase III, evaluations were informed by interviews with change leaders, follow‐up measures of staff knowledge and a nurse focus group. Qualitative data were thematically analysed. Statistical analyses compared nurses' knowledge over time. Results: Planned practice change included nurses providing information packs to caregivers, then engaging in, and documenting, a systematic conversation. From 32 caregivers, 15 received information packs, five conversations were initiated, and one was completed. Knowledge of dementia and Alzheimer's disease improved significantly in change leaders ( n = 7) and other nurses ( n = 17). Three change leaders were interviewed, and six other nurses contributed focus group data. These leaders reported feeling motivated and suitably prepared. Both nurses and leaders recognised potential benefits from the planned conversation but viewed it as too time‐consuming to be feasible. Conclusions: The communication initiative and implementation strategies require further tailoring to the clinical setting. A caregiver communication tool may be a helpful adjunct to the conversation. Implementation may be enhanced by more robust stakeholder engagement, change leader inclusion in the reference group and an overarching supportive framework within which change leaders can operate more effectively. Implications for Practice: Nurse‐caregiver communication in this context requires inititatives tailored to the clinical setting with input from all stakeholders.